PERBANDINGAN METODE KNN DAN SVM DALAM KLASIFIKASI KEMATANGAN BUAH MANGGA BERDASARKAN CITRA HSV DAN FITUR STATISTIK - Mutmainnah Muchtar; Rafiqah Arjaliyah Muchtar (Universitas Lampung, 2024)
This research compares the classification methods of K-Nearest Neighbors (KNN) and Support Vector Machine (SVM) in identifying the ripeness level of mango fruit based on HSV images and statistical features. A total of 80 mango fruit images were categorized into two classes, namely